2010
DOI: 10.2134/jeq2009.0216
|View full text |Cite
|
Sign up to set email alerts
|

Soil Properties and Trace Elements Contents Following 40 Years of Phosphate Fertilization

Abstract: Long-term application of P fertilizers may eventually result in excess and/or toxic accumulations of trace elements and microelements in soil. The effect of monoammonium-phosphate (MAP) on basic soil properties (pH, CEC, texture), the total content of C, N, and F, hot acid-extractable Cu, Zn, Ni, Cr, Pb, Cd, Co, As, Hg, and F, and the content of extractable macro- and trace elements (P, K, Ca, Mg, Al, Fe, Zn, Cu, Ni, Pb, Cd, F) were studied on a Stagnosol soil. Phosphate fertilizer had been applied (26, 39, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 45 publications
2
15
1
5
Order By: Relevance
“…According to Table 3 and 4, Limau Manis and Selapon have the highest amount of P (9.7 mg/kg) and manganese (406.1 mg/kg) among the study. The same findings were reported by [7,13,14] Cd is associated with manganese-oxide in soil andtriple superphosphate (TSP) fertilizer was primary supply of Cd toward soils as it has 0.1-170 mg/kg of Cd. We observed that TSP used by Brunei Darussalam carried 2.87 mg/kg of Cd.…”
Section: Heavy Metals Statussupporting
confidence: 76%
“…According to Table 3 and 4, Limau Manis and Selapon have the highest amount of P (9.7 mg/kg) and manganese (406.1 mg/kg) among the study. The same findings were reported by [7,13,14] Cd is associated with manganese-oxide in soil andtriple superphosphate (TSP) fertilizer was primary supply of Cd toward soils as it has 0.1-170 mg/kg of Cd. We observed that TSP used by Brunei Darussalam carried 2.87 mg/kg of Cd.…”
Section: Heavy Metals Statussupporting
confidence: 76%
“…Soil organic carbon (C) was measured using the Tjurin method (Nelson & Sommers 1996) and total nitrogen (N) using the Kjeldahl method (Bremner 1960, ISO-11261 1995. After extraction, the available P and K were determined by the Egner-Riehm method (Cakmak et al 2010). All analyses were performed in 2 replicates.…”
Section: Soil and Litter Propertiesmentioning
confidence: 99%
“…Heavy metal stress is becoming a major challenge to crop plants, particularly to vegetable crops, because of soil contamination. These heavy metals are derived from city/industrial effluent (Cai et al, 2010(Cai et al, , 2012Wang et al, 2013), electronic waste recycling/dismantling activities Zheng et al, 2011;Liu et al, 2013), mining and smelting (Zhao et al, 2012;Tai et al, 2013), fertilizers and pesticides (Brady and Weil, 1996;Atafar et al, 2010;Cakmak et al, 2010;Nacke et al, 2013;Yu et al, 2013), and auto mobile depositions (Turer et al, 2001(Turer et al, , 2003; additionally, waste water/sewage water can be a major source of heavy metals in areas where raw sewage water is used for irrigation Wang et al, 2013). As heavy metals are not biodegradable and can accumulate in human organs, ingestion of vegetables that have been irrigated with contaminated water poses a serious risk to human health.…”
Section: Introductionmentioning
confidence: 99%